The Role of Parents in Children's Achievement in Cimahi United Football School - Rifqi fajar Andriawan; Budiman; Agus Santosa (STKIP Pasundan Press, 2025)
The Role of Parents in Children's Achievement in Cimahi United Football School. The purpose of this study was to determine how big the role of parents is in supporting children's achievements in Cimahi United football school. This study is a type of quantitative description research using a survey method, from the results of the study obtained, the researcher took all 18 parents as samples, the researcher used a questionnaire with a total of 35 questions that had been tested for validity and rehabilitation. The data collection technique used was by distributing questionnaires directly using sheets of paper to 18 respondents. After the data was collected, the data was analyzed using a percentage formula with the results of the study of the role of parents towards children's achievements at the Cimahi United soccer school